The Basis Number of Mycielski ’s Graph for Some Cog- Graphs (European Journal of Pure and Applied Mathematics, 2023)
Let G = (V, E) be a simple connected graph, then the basis number of G is denoted by b(G) and is defined by the least positive integer k such that the graph G has a k − fold basis for it is cycle space. In this paper we studied the basis number of Mycielski’s graph for some cog-special graphs, and we compute the basis number of Mycielski’s graph for cog-path graph, cog-cycle graph, cog-star graph, and cog-wheel graph.
Keywords: Basis number , k-fold , Mycielski’s graph